Counteracting stacking; enabling people in the Swedish asylum process to spatially influence their living environment - Nederman Thore, Maja (My University, 2025)
This thesis critically examines the furnishing of the rooms and sleeping places allocated to each asylum seeker in a Swedish asylum accommodation. The aim is to see how the architect can contribute to the global humanitarian problem that is forced displacement and refugeeism through analyzing and visualizing the environments and spaces connected to it - as well as investigate how spatial interventions can counteract the asylum seeker’s lack of influence. The underlying idea is to highlight the importance of design by strengthening the link between the built environment and the humanitarian rights of the individual. In this way, an organisation such as the Migration agency which is used to consulting other professions rather than architects on these issues can be motivated to do so. To understand and explain the complex structures that are Swedish integration and asylum reception, methods have ranged from reading international law and interviewing staff working in the accommodations - to challenging classic architectural drawing language by instead showcasing information through various types of storytelling. More specifically, the work examines the facilities that the asylum seeker live in during the two earlier stages of their arrival in Sweden. These two types of accommodations are exemplified via Sagåsen arrival accommodation in Kållered outside Gothenburg, together with the long-term accommodation Restad Gård in Vänersborg. The study points to the fact that there are many structural and administrative factors that prevent asylum accommodations from both spatially individualizing but also changing in general. The keys to unlocking these bureaucratic locks are small, precise and allow residents to both customize and create a relationship with the environment they are living in. Proposed is a small catalog of 6 architectural keys, or interior objects, that can be implemented in the already rigid context of the rooms. The objects work to counteract the feeling of temporarity and instead enable conditions to store one’s belongings and strengthens the individual’s possibility to choose the amount of lighting and privacy by their own space.
Keywords: Asylum accommodations, Small scale interventions, Swedish migration agency, Refugee architecture, Personalization, Bunk bed